A case of fever of unknown origin and abdominal mass - Ahmed, M; Patwary, MI; Ansari, MAJ; Choudhury, MSR (Journal of Dhaka Medical College, 2012)
DOI: http://dx.doi.org/10.3329/jdmc.v20i2.10552 J. Dhaka Med. Coll. 2011; 20(2): 210-212